2021
DOI: 10.3390/insects12080741
|View full text |Cite
|
Sign up to set email alerts
|

Aphid Odorant-Binding Protein 9 Is Narrowly Tuned to Linear Alcohols and Aldehydes of Sixteen Carbon Atoms

Abstract: Aphid odorant-binding protein 9 is almost exclusively expressed in antennae and is well conserved between different aphid species. In order to investigate its function, we have expressed this protein and measured ligand-binding affinities to a number of common natural compounds. The best ligands are long-chain aldehydes and alcohols, in particular Z9-hexadecenal and Z11-hexadecenal, as well as 1-hexadecanol and Z11-1-hexadecenol. A model of this protein indicated Lys37 as the residue that is likely to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…FCBA result showed that GOBP with broad spectrum, such as CsasGOBP1–2 displayed high binding affinity to general components of plant volatiles [ 31 ] and CpunGOBP2 displaying the widest binding spectra [ 23 ]. Furthermore, ApisOBP9 shows high and specific affinity to linear alcohols and aldehydes of 16-carbon [ 48 ] and EoblOBP6 binds the tea plant volatile, benzaldehyde and display high binding ability to herbivore-induced plant volatiles (HIPVs), nerolidol and α-farnesene [ 49 ] with the narrow spectrum. Similarity, in our previous studies, FCBA result showed that EsigGOBP1 mainly bind benzene, 1,2-diethyl-, alpha-phellandrene, butyl acrylate and camphene.…”
Section: Discussionmentioning
confidence: 99%
“…FCBA result showed that GOBP with broad spectrum, such as CsasGOBP1–2 displayed high binding affinity to general components of plant volatiles [ 31 ] and CpunGOBP2 displaying the widest binding spectra [ 23 ]. Furthermore, ApisOBP9 shows high and specific affinity to linear alcohols and aldehydes of 16-carbon [ 48 ] and EoblOBP6 binds the tea plant volatile, benzaldehyde and display high binding ability to herbivore-induced plant volatiles (HIPVs), nerolidol and α-farnesene [ 49 ] with the narrow spectrum. Similarity, in our previous studies, FCBA result showed that EsigGOBP1 mainly bind benzene, 1,2-diethyl-, alpha-phellandrene, butyl acrylate and camphene.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant protein EcorOBP15-m1 was expressed in E. coli using standard protocols. , In order to solubilize the protein, the pellet was dissolved with 8 M urea/5 mM DTT for 1 h at room temperature and then dialyzed for 3 days against 50 mM Tris HCl pH 7.4 at 4 °C. The solubilized protein was then purified by two chromatographic steps on anion-exchange HiPrep-Q (GE-Healthcare) column.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of OBP genes have been identified in aphids, and OBP3/7 from Sitobion avenae , Rhopalosiphum padi and Acyrthosiphon pisum were discovered to detect semiochemicals 14–17 . In particular, OBP9 from M. persicae , S. avenae and A. pisum exhibited stronger binding ability toward semiochemicals than OBP3 and OBP7, 18–21 indicating that OBP9 is critical in recognizing natural semiochemicals and their analogs in insect chemical communication systems.…”
Section: Introductionmentioning
confidence: 99%